What Happens beyond the Screen? Uncovering Digital Technology Perception, Usage, and Parental Mediation among 3–6-year-old Turkish Children - Ata-Aktürk, Aysun; Akman, Müzeyyen Büşra (Springer Science and Business Media LLC, 2024)
AbstractThis study aims to investigate digital technology (DT) perceptions and usage among 3–6-year-old Turkish children. Children (N = 293) were asked to imagine themselves using DT, draw pictures of what they imagine, and narrate their drawings. They then were interviewed about their DT use. Parents (N = 293) also participated via a questionnaire addressing the digital environment, screen time (ST), and parental mediation (PM) of children’s technology use. Using a mixed-method approach, qualitative data were subjected to content analysis and converted to quantitative data. The quantitative analysis involved Kruskal–Wallis H, Mann–Whitney U, Spearman’s rho, and Chi-square tests. Findings indicated children may have limited perception regarding the usage alternatives of DTs, no significant difference between the purpose of DT use in drawings in terms of gender, an average ST of three hours among children, a moderate positive correlation between children’s and parents’ ST, and children primarily engaging in watching and playing activities. While children’s ST did not differ according to age, it varied significantly according to the parents’ educational levels. According to the rating systems, children are exposed to games and content that are not age-appropriate. Parents mainly mediate their children’s DT usage by limiting ST and accompanying children’s screen use. The study includes implications and suggestions for parents, educators and schools, community, content developers, digital platforms, and researchers working on this subject to work collaboratively to ensure that young children use digital technologies interactively, supporting development and education, and in age-appropriate, creative usage alternatives.
Keywords: 4. Education